1999
DOI: 10.1046/j.1525-1500.1999.99049.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival Differences in Breast Cancer among Racial/Ethnic Groups: A Population-Based Study

Abstract: In women, breast cancer is the most frequent solid tumor and the second leading cause of cancer death. Differences in survival of breast cancer have been noted among racial/ethnic groups, but the reasons are unclear. This report presents the characteristics and the survival experience of four racial/ethnic groups and evaluates the effects of stage, age, histology, and treatment on survival time. The distributions of prognostic factors and treatment among racial/ethnic groups are compared using female breast ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
68
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(73 citation statements)
references
References 24 publications
4
68
0
1
Order By: Relevance
“…[5][6][7][8][9][10][11] One of the reasons for these disparities in breast cancer outcomes is the well-documented tendency toward later stage at diagnosis among women of lower socioeconomic status (SES) and women of color. 5,8,9,[12][13][14] Differences in mammography utilization are widely believed to contribute to observed socioeconomic and racial/ethnic variation in prevalence of late-stage diagnosis. Despite recommendations for routine annual or biannual mammography for all women age 40 years and older, significant gaps exist in uptake across population subgroups.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11] One of the reasons for these disparities in breast cancer outcomes is the well-documented tendency toward later stage at diagnosis among women of lower socioeconomic status (SES) and women of color. 5,8,9,[12][13][14] Differences in mammography utilization are widely believed to contribute to observed socioeconomic and racial/ethnic variation in prevalence of late-stage diagnosis. Despite recommendations for routine annual or biannual mammography for all women age 40 years and older, significant gaps exist in uptake across population subgroups.…”
Section: Introductionmentioning
confidence: 99%
“…5,6,12 Although the black/white survival disparity in breast carcinoma is well documented, few studies of racial/ethnic disparities have addressed the survival experience of other racial/ethnic groups. Like black women, Hispanic women also tend to be diagnosed with breast carcinoma at a later stage than white women, but it is unclear if Hispanic females have poorer survival.…”
mentioning
confidence: 99%
“…Like black women, Hispanic women also tend to be diagnosed with breast carcinoma at a later stage than white women, but it is unclear if Hispanic females have poorer survival. 9,[12][13][14][15] International studies of breast carcinoma have shown better survival for Japanese than Caucasians, 16 but most studies report similar survival rates for Asians and whites within the United States. 12,[17][18][19] In addition, although race/ethnicity, disease stage, and SES are correlated, SES measures have not been included in most studies of Asian and Hispanic women.…”
mentioning
confidence: 99%
“…In contrast, patients with ER-negative tumours are often given chemotherapy. Boyer-Chammard et al (1999) reported that African-American, Hispanic, and Asian patients with breast cancer from 1984 through 1990 were more likely than Caucasian patients to receive chemotherapy and less likely to receive endocrine therapy. The current study is similar to those results.…”
Section: Lymph-node Statusmentioning
confidence: 99%
“…Asian-American and Japanese patients tend to have a lower incidence of breast cancer and have a better prognosis than Caucasians (Yonemoto, 1980;Sakamoto et al, 1981;Natarajan et al, 1988;Tominaga and Kuroishi, 1995;Boyer-Chammard et al, 1999;Braun et al, 2004). Age-adjusted incidence rate for breast cancer among Japanese patients has markedly increased 1.9-fold from 1978 to 1998 (age-adjusted incidence rate: 17.9, 33.8, respectively) (The Research Group for Population-based Cancer Registration in Japan, 1999Japan, , 2003Tamakoshi et al, 2005) and age-adjusted death rate has increased moderately (Tominaga and Kuroishi, 1995), but is still much lower compared with those of Caucasians (Tominaga and Kuroishi, 1995;Kawamura and Sobue, 2005).…”
mentioning
confidence: 99%